2013
DOI: 10.4037/ccn2013204
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Ventilator-Associated Pneumonia in Children: An Evidence-Based Protocol

Abstract: A s a hospital-acquired infection (HAI), ventilator-associated pneumonia (VAP) is associated with additional complications for patients in the pediatric intensive care unit (PICU). Despite the volume of published information on VAP in adults, the amount of research on VAP in children is limited. Health care providers need to be aware of the risk for VAP in infants and children and should have preventive programs in place. Evidence-based protocols that outline preventive and therapeutic treatments for specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 26 publications
(52 reference statements)
0
36
0
Order By: Relevance
“…24,32,35 The use of distilled or sterile water showed no undesired effect and was indicated for being an effective method in assisting the removal of residues that may be in the oral cavity, in a safely manner since they occur in their neutral form and free from impurities. 5,14,15,34,35,37 In adults, we observed that the main substance used and recommended was the 0.12% chlorhexidine digluconate due to its bactericidal and bacteriostatic effects for up to 12 hours, and with wide range of bacterial reduction both aerobic and anaerobic, Gram-positive and Gram-negative. 1,2,[4][5][6]18,23 The 0.12% chlorhexidine digluconate was recommended at different concentrations by 14 authors; however, the majority indicated its use only in PICU.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…24,32,35 The use of distilled or sterile water showed no undesired effect and was indicated for being an effective method in assisting the removal of residues that may be in the oral cavity, in a safely manner since they occur in their neutral form and free from impurities. 5,14,15,34,35,37 In adults, we observed that the main substance used and recommended was the 0.12% chlorhexidine digluconate due to its bactericidal and bacteriostatic effects for up to 12 hours, and with wide range of bacterial reduction both aerobic and anaerobic, Gram-positive and Gram-negative. 1,2,[4][5][6]18,23 The 0.12% chlorhexidine digluconate was recommended at different concentrations by 14 authors; however, the majority indicated its use only in PICU.…”
Section: Discussionmentioning
confidence: 94%
“…Among the most recommended substances for toothless newborns and babies, we have: bicarbonate water at 3%, 24,34 enzymatic solution based on lactoperoxidase, 24,32 hydrogen peroxide, 24,35 distilled or sterile water 14,15,34,35,37 and saline solution. 14,29 It is crucial to be careful on the guidance on adjuvant solutions to the mechanical methods used in the cleaning of the oral cavity due to risk of damage to the oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers implemented a modified paediatric ventilator bundles which were adapted from adult VAP bundles (Weber, ). Ventilator bundles that include head of the bed elevation, clean endotracheal suctioning practices, minimal ventilator circuit changes, peptic ulcer prophylaxis and oral care are recommended in paediatrics (Cooper & Haut, ). However, there are variations in the ventilator bundle interventions implemented to prevent VAP in paediatric populations.…”
Section: Introductionmentioning
confidence: 99%